2018
DOI: 10.1172/jci.insight.93936
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-induced glucagon-like peptide-1 secretion contributes to the actions of metformin in type 2 diabetes

Abstract: BACKGROUND. Metformin reduces plasma glucose and has been shown to increase glucagon-like peptide 1 (GLP-1) secretion. Whether this is a direct action of metformin on GLP-1 release, and whether some of the glucose-lowering effect of metformin occurs due to GLP-1 release, is unknown. The current study investigated metformin-induced GLP-1 secretion and its contribution to the overall glucose-lowering effect of metformin and underlying mechanisms in patients with type 2 diabetes. METHODS. Twelve patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 73 publications
(89 reference statements)
1
98
1
1
Order By: Relevance
“…However, the similar findings were noted in the voglibose and the placebo group, which can be attributed to the comparable magnitude of weight reduction in these participants, hence negating the insulin‐sensitizing effect of metformin. Intriguingly, the HOMA‐β indices were found to be modestly higher in the metformin‐treated group, which could be ascribed to the reduction in glucotoxicity, and glucagon‐like peptide 1 (GLP‐1)‐mediated improvement in β‐cell function, as metformin also stimulates GLP‐1 secretion . Further, upregulated mitophagy could have also contributed to the improved β‐cell function, as strengthened by regression analysis, which revealed a positive association of HOMA‐β indices with a key mitophagy player PINK1.…”
Section: Discussionmentioning
confidence: 89%
“…However, the similar findings were noted in the voglibose and the placebo group, which can be attributed to the comparable magnitude of weight reduction in these participants, hence negating the insulin‐sensitizing effect of metformin. Intriguingly, the HOMA‐β indices were found to be modestly higher in the metformin‐treated group, which could be ascribed to the reduction in glucotoxicity, and glucagon‐like peptide 1 (GLP‐1)‐mediated improvement in β‐cell function, as metformin also stimulates GLP‐1 secretion . Further, upregulated mitophagy could have also contributed to the improved β‐cell function, as strengthened by regression analysis, which revealed a positive association of HOMA‐β indices with a key mitophagy player PINK1.…”
Section: Discussionmentioning
confidence: 89%
“…Studies using the GLP‐1 receptor antagonist, exendin (9‐39), in animals and humans have shown that blocking GLP‐1 receptor signalling reduces glucose‐lowering by metformin substantially, indicating that GLP‐1 has a major role in mediating this effect of metformin. For example, in insulin‐resistant rats, during a euglycaemic clamp, intraduodenal metformin failed to increase the glucose infusion rate in the presence of exendin (9‐39) and in patients with T2DM, oral metformin stimulated GLP‐1 secretion and the associated glucose‐lowering was attenuated by exendin (9‐39) …”
Section: Gastrointestinal Effects Of Metformin: Role Of Gut Peptidesmentioning
confidence: 99%
“…The effect of metformin to increase GLP‐1 secretion has been observed in health and T2DM, albeit inconsistently. In acute experimental settings, a single dose of metformin (between 850 mg and 1500 mg) was reported to increase fasting and postprandial GLP‐1 concentrations in some, but not all, studies. However, studies relating to administration of metformin for between 4 weeks and 18 months have more consistently shown elevations in GLP‐1, although one study failed to observe an effect .…”
Section: Gastrointestinal Effects Of Metformin: Role Of Gut Peptidesmentioning
confidence: 99%
See 2 more Smart Citations